Adoption of Sprinkler Irrigation System by the Farmers in Gujarat (Indian Journal of Extension Education, 2014)
The study was conducted in Dantiwada and Deesa talukas of Banaskantha district of north Gujarat to assess the extent of adoption of sprinkler irrigation system. From each taluka six villages selected purposively and from each village 10 farmers were selected by using random sampling technique, there by constituting a total sample size of 120 respondents. Data were collected by using personal interview method. However, majority of farmers were found having medium level of adoption in sprinkler irrigation system. Education, land holding, social participation, annual income, source of information, knowledge level, economic motivation, source of irrigation, cropping pattern and cropping intensity had significantly associated with their extent of adoption of sprinkler irrigation system.